(untitled) (Research, Society and Development, 2020)
The objective of the present study was to evaluate the leaf area, chlorophyll a, b and total and the SPAD index of sunflower grown under different water deficit conditions and fertilization levels with mineral and organomineral NPK. The experiment was conducted in plastic vases filled with dystrophic Red Latosol, located in an experimental area of the Federal Goiano Institute, in the municipality of Rio Verde, Goiás. The experimental design used was the randomized blocks analyzed in a 4 × 4 × 2 factorial scheme, with three repetitions. The treatments were the combinations of four water replacements equal to 50, 75, 100 and 125% of the available water capacity in the soil; four doses of the formulated NPK referring to 50, 100, 150 and 200% of the recommendation and two sources of the formulated NPK, mineral and organomineral. Water replacements were determined using electronic weighing lysimeters and water applied via a surface drip system. The number of leaves, leaf area, chlorophyll a, chlorophyll b, total chlorophyll and the SPAD index were evaluated at 20, 40, 60 and 80 days after sowing. The water replacement of 125% provides the largest number of leaves and leaf area of sunflower cv. Aguará 6. The number of leaves, leaf area and SPAD index of sunflower cv. Aguará 6 is higher when using mineral fertilizer.